Factors influencing adherence to antiretroviral therapy from the experience of people living with HIV and their healthcare providers in Sierra Leone: a qualitative study - Michael Lahai; Sally Theobald; Haja R. Wurie; Sulaiman Lakoh; Patrick O. Erah; Mohamed Samai; Joanna Raven (BMC, 2022)
Abstract Background Antiretroviral therapy (ART) is the primary mode of treatment for Human Immunodeficiency Virus (HIV). It slows disease progression and reduces the spread of infection. HIV treatment is also known to require a high level of adherence of over 90% to achieve good treatment outcomes and viral load suppression. In Sierra Leone, about 70% of People Living with HIV (PLHIV) are non-adherent in their first year of treatment. Understanding the reasons behind this high rate of non-adherence from the perspectives of both PLHIV and health workers is critical for developing strategies to improve adherence. This qualitative study is rooted in the field of public health services. It identifies the barriers and facilitators influencing adherence to antiretroviral treatment in Sierra Leone.  Methods A qualitative study design using in-depth interviews of four healthcare workers and 16 PLHIV in two districts in Sierra Leone- Freetown and Bo. The interviews were analyzed using a grounded theory approach to identify emerging themes from the data. Results The study identified several facilitators and barriers to ART adherence at the personal, community, and health system levels. The facilitators included perceived benefits of ART, family support, having an informal caregiver, receiving free ART medicines, and belonging to peer support groups. The identified barriers were stigma and discrimination, frequency of medication, use of traditional medicine, lack of money for food and transport, work barriers, inadequate medicines and test kits, limited health workers, and long distances to clinics. Conclusions Our study emphasized the need for implementing behavioural change communication programmes and activities to reduce stigma and discrimination in the community. Knowledge of the facilitators and barriers to antiretroviral therapy could provide relevant information for more responsive and equitable programmes supporting adherence implementation in low- and middle-income countries. This study also identifies the vital need for community integration of HIV treatment services.